Влияние криодеструкции с аутовакцинацией на некоторые параметры клеточного и гуморального иммунитета больных раком молочной железы - Тащиев, Р.К.; Абраменко, И.В.; Шляховенко, В.А.; Ашраф Авад Эль Карим (Онкологія, 2006)
Summary. Tumor cryodestruction with subsequent surgery and cryoautovaccination was performed in 22 breast cancer patients, including 5 at stage IIa (T1-2N0-1M0); 9 at stage IIb (T2-3N0-1M0), 7 at stage IIIa (T2-3N2M0); and 1 at stage IIIb (T4N0-3M0). Patients tolerated the combined treatment without general and local side effects and resulted in a significantly decreased concentration of СА15-3 antigen in the blood serum, increased helper-to-suppressor ratio, tendency to increased numbers of CD3+- and CD4+-T lymphocytes, development of delayed-type hypersensitivity and appearance of serum antibodies to the vaccine’s components. Over the follow-up period (12 to 28 months) all patients were alive with no signs of relapse. These findings suggest that it is promising to continue investigation in this direction.